Investigation of the influence of varying tumbling strategies on a tumbling self-piercing riveting process - Wituschek, Simon; Kappe, F.; Lechner, Michael (Production Engineering, 2021)
The increasing demands for the reduction of carbon dioxide emission require intensified efforts to increase resource efficiency. Especially in the mobility sector with large moving masses, resource savings can contribute enormously to the reduction of emissions. One possibility is to reduce the weight of the vehicles by using lightweight technologies. A frequently used method is the implementation of multi-material systems. These consist of dissimilar materials such as steel, aluminium or plastics. In the production of these systems, the joining of the different materials and geometries is a central challenge. Due to the increasing demands on the joints, the challenges for the joining processes itself are also increasing. Since conventional joining processes are rather rigid and can only react to a limited extent to disturbance variables or changing process variables, new methods and technologies are required. A widely used conventional joining method with these properties is self-piercing riveting. Because of the rigid tool combination and the fact that the rivet geometry that can be used is related to the tools, the joining of multi-material systems requires tool and rivet changes during the process. In order to extend the process window of joining with self-piercing rivet elements, the process is enhanced with a tumbling kinematic of the punch. The integration of tumbling results in a significant increase in the adjustable process parameters. This enables a higher material flow control in the joining process through a specific tumbling strategy. The materials investigated are a steel and an aluminium alloy, which differ significantly in their mechanical properties and have many applications in automotive engineering, especially for structural car body components. The steel material is a galvanized HCT590X+Z dual-phase steel, which is characterised by a low yield strength, combined with high tensile strength and a good hardening behaviour. The aluminium alloy is an EN AW-6014. The precipitation-hardening alloy consists of aluminium, magnesium and silicon with a high strength and energy absorption capability. The objective of this work is to obtain a fundamental knowledge of the new tumbling self-piercing riveting process. With different mechanical properties and different sheet thicknesses of the joining partners, the influences of these parameters on the tumbling strategy of the riveting process are analysed. Such a tumbling strategy is based on the tumbling angle, the tumbling onset and the tumbling kinematics. These parameters are investigated in the context of the work for selected combinations of multi-material systems consisting of HCT590X+Z and EN AW-6014. With the variation of the parameters, the versatility of the process can be investigated and influences of the tumbling on the self-piercing riveting process can be identified. To illustrate the results, force-displacement curves from the joining process of the individual joints are compared and the geometry of the rivet undercut and rivet heads are geometrically measured. Furthermore, micrographs allow the analysis of the characteristic joint parameters interlock, residual sheet thickness and end position of the rivet head.
CRIS-Team WoS Importer:2022-01-14